Crystal structure of [(2R, 3R, 4S)-3, 4-bis(acetyloxy)-5-iodo-3, 4-dihydro-2Hpyran-2-yl]methyl acetate. (January 2015) - Zukerman-Schpector, Julio; Caracelli, Ignez; Stefani, He´lio A.; Shamim, Anwar; Tiekinke, Edward R.T.
No abstract available